2017
DOI: 10.1590/s0103-73312017000300003
|View full text |Cite
|
Sign up to set email alerts
|

O trabalho de parto do obstetra: estilo de pensamento e normalização do “parto cesáreo” entre obstetras

Abstract: Resumo: O artigo objetiva compreender aspectos da formação de um estilo de pensamento que convergem para a ideia da cirurgia como uma forma de parto simples e de poucos riscos, a partir da análise de relatos de obstetras do Rio de Janeiro sobre a utilização da cesariana. Guiados pelo método de relatos orais, discutimos a construção de uma prática obstétrica que vê a cesariana como indicação adequada para qualquer situação de parto; a agregação de diferentes valores à cesariana, a partir de seu desenvolvimento … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
27

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 15 publications
1
8
0
27
Order By: Relevance
“…Rev Gaúcha Enferm. 2018;39:e20170218 This result corroborates studies that demonstrate the importance and the benefit of the presence of a companion in the process of parturition (16,(18)(19)(20) . An international study carried out in a hospital that partially prohibits the participation of family members has shown that, although women prefer to be accompanied by their relatives, they feel satisfied with the company of health professionals, especially when the care offered is comprehensive and humanized, since they consider it as a way of not feeling alone (14) .…”
Section: [] When the Contraction Passes You Do Not Feel Anything supporting
confidence: 81%
See 1 more Smart Citation
“…Rev Gaúcha Enferm. 2018;39:e20170218 This result corroborates studies that demonstrate the importance and the benefit of the presence of a companion in the process of parturition (16,(18)(19)(20) . An international study carried out in a hospital that partially prohibits the participation of family members has shown that, although women prefer to be accompanied by their relatives, they feel satisfied with the company of health professionals, especially when the care offered is comprehensive and humanized, since they consider it as a way of not feeling alone (14) .…”
Section: [] When the Contraction Passes You Do Not Feel Anything supporting
confidence: 81%
“…The ND pain is commonly explored by professionals to coerce women to choose the cesarean section, in conjunction with the idea of the safety provided by it (16) . The women in this study did not suffer from this type of approach, most probably because of the safety and certainty demonstrated by the option for the ND and the internal agreement they had to make efforts to experience it.…”
Section: Since the First Pregnancy I Always Knew That I Wanted A Normmentioning
confidence: 99%
“…However, research shows that this practice was not abandoned in Brazil (Poterr et al, 2003;Carvalho et al, 2007;Castro et al, 2007). In addition to all of these reasons, obstetricians agree with the premise that this type of birth is not a medical recommendation in emergency cases, but a woman's "choice" (Faundes and Cecatti, 1991;Nakano et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Há evidências de que a inclinação das gestantes pelo parto natural, em condições normais, contrasta com os elevados índices de cesarianas encontrados no município estudado, sinalizando para a existência de outros fatores que influenciam na decisão. Ao vivenciar uma cesariana as puérperas podem ter sua recuperação dificultada e isso pode ocasionar um contato tardio entre mãe e bebê, além de ser um obstáculo às posições mais confortáveis para a amamentação, tornar-se um óbice ao autocuidado, ao cuidado do recém-nascido e à realização das atividades cotidianas da mulher (13)(14)(15)(16)(17) .…”
Section: Discussionunclassified